2021
DOI: 10.1149/1945-7111/abfab7
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Electrochemical Analyses for Dysprosium Complexes In Potassium Bis(trifluoromethylsulfonyl)amide Melts

Abstract: The coordination states of multivalent dysprosium complexes of potassium bis(trifluoromethylsulfonyl) amide (K[NTf2]) were investigated by Raman spectroscopy. The concentration dependence of the deconvoluted Raman spectra was investigated for 0.23−0.45 mol kg−1 Dy(III), and a mixed sample of Dy(II)/Dy(III) (molar ratio 1/3), in K[NTf2]. Using conventional analysis, the solvation number, n, of the dysprosium complexes was determined to be 4.12 for Dy(II) and 5.09 for Dy(III). The electrochemical behavior of [Dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The original peak at 741 cm −1 is due to "free" [ ] − Tf N 2 anion and the new band at 752 cm −1 is attributed to [ ] − Tf N 2 anion bounded to the center of Sm 3+ cation as observed for other lanthanides ions in ionic liquid systems. [33][34][35][36] To obtain some quantitative information in the dissolution of the samarium salt in the ionic liquid, Raman spectra of 0.3 M, 0.4 M and 0.5 M of Sm(Tf 2 N) 3 in [BMP][Tf 2 N] were acquired within the range of 720-780 cm −1 and the bands at 741 cm −1 and 752 cm −1 are deconvoluted and fitted with two Voigt functions as shown in Fig. 3.…”
Section: Raman Spectroscopic Analysis Of Sm(iii) Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The original peak at 741 cm −1 is due to "free" [ ] − Tf N 2 anion and the new band at 752 cm −1 is attributed to [ ] − Tf N 2 anion bounded to the center of Sm 3+ cation as observed for other lanthanides ions in ionic liquid systems. [33][34][35][36] To obtain some quantitative information in the dissolution of the samarium salt in the ionic liquid, Raman spectra of 0.3 M, 0.4 M and 0.5 M of Sm(Tf 2 N) 3 in [BMP][Tf 2 N] were acquired within the range of 720-780 cm −1 and the bands at 741 cm −1 and 752 cm −1 are deconvoluted and fitted with two Voigt functions as shown in Fig. 3.…”
Section: Raman Spectroscopic Analysis Of Sm(iii) Inmentioning
confidence: 99%
“…However, the obtained solvation number of 4 for Sm 3+ in the present study is closer to the calculated value of 5 for Nd 3+ and Dy 3+ in a Tf 2 N-based ionic liquid. 34,35,37,42 [ ] − Tf N 2 is known to act as a bidentate ligand with its two oxygen atoms coordinating to the central Sm 3+ . Table SII summarizes some reported Ln complexes in both ionic liquids and neutral ligandbased ionic liquid systems.…”
Section: Raman Spectroscopic Analysis Of Sm(iii) Inmentioning
confidence: 99%
“…We also showed that the solvation structures and the electrochemical behaviors of the trivalent Nd(III) and Dy(III) have been investigated in our previous study [7,8] in order to elucidate the mechanism of electrodeposition. However, there was no information on the detailed solvation conformations of Pr(III) in K[NTf2] melts.…”
Section: Introductionmentioning
confidence: 99%
“…Environmentally, LTMS is stable compared to organic reagents and prevents the spread of harmful degradation products, as LTMS can be recycled back into the acid production cycle and re-used as an electrolytic bath. Recent work has revealed the electrochemical and nucleation behavior of Nd(III) [7] and Dy(III) [8] within the K[NTf2] melts. However, there was no information available on the diffusion and electrodeposition behavior of Pr(III) in K[NTf2] melts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation